(untitled) (ҚазҰУ Хабаршысы. География сериясы, 2025)
Precise monitoring of surface water storage dynamics is crucial for effective water resource management and comprehension of local hydrological processes. This study examines the correlation between fluctuations in water levels in the Zhaiyk River Basin (Ural) and anomalies in overland water storage derived from the Gravity Recovery and Climate Experiment (GRACE) satellite gravimetry. We assess the degree of the satellite-in situ measurement correlation using long-term hydrological observations and GRACE equivalent water thickness data. With a coefficient of determination (R2) of 0.7459, the results show a noteworthy positive correlation, indicating that GRACE data capture regional large-scale hydrological changes. Nevertheless, the study also highlights the coarse spatial resolution of GRACE, which limits its ability to detect local water level fluctuations. GRACE continues to be an invaluable instrument for evaluating the dynamics of long-term water storage and its underlying factors, such as precipitation, evapotranspiration, and anthropogenic influences. Future research should investigate the feasibility of integrating GRACE with hydrological models and higher-resolution remote sensing products to enhance the precision of monitoring and broaden the scope of satellite gravity’s application in regional water resources assessment